AVALIAÇÃO DO LANÇAMENTO DE LODO DE ETA ACTIFLOÒ EM ETE COM REATOR ANAERÓBIO NO MUNICÍPIO DE PONTA GROSSA – PR - WAGNER, LUIZ FERNANDO (2015)
The disposal of wastes generated in water treatment plants (WTP) by launching into water streams is considered an environmental crime by current Brazilian law and became one of the challenges of drinking water public companies, nowadays. The objective of this study was to analyze the alternative disposal of decanter’s sludge from a WTP, with microsand ballasted sedimentation (ActifloÒ), in a wastewater treatment plant (WWTP) containing upflow anaerobic sludge blanket reactors (UASB) and polishing pond, called WWTP Verde, in the city of Ponta Grossa - PR, through the sewage collection network. The treatment evaluation on the WWTP was performed for seven distinct phases. The phase 1 occurred with WWTP receiving only sewage. Phases 2 to 7 occurred with release of WTP sludge in continuous periods ranging from 4 hours per day (phase 2) to 24 hours per day (phase 7), reaching the percentage of 3.2% of WTP sludge, in relation to the total volume tributary to WWTP. The WWTP operated in stable condition throughout the period, with an average flow tributary of 213.14 L/s. The UASBs operated with HRT in 9.9 hours, VHL in 2.4 m3/m3/d, and OLR ranging from 0.75 to 1.66 kgCOD/m3/d. The polishing pond operated with HRT in 4.5 days and OLR ranging from 765 to 2872 kgCOD/ha/d, which corresponds from 19 to 72 gCOD/m3/d. The removal efficiency of COD and TSS by UASBs and the pond was maintained even with the release of WTP sludge. The overall efficiency of the WWTP ranged between 80% and 86% for COD removal and between 92% and 96% for the TSS removal. It was observed greater removal of nitrogen and phosphorus by UASBs and higher concentration of nitrogen, phosphorus, potassium and magnesium in the UASB's sludge, in the period in which the WWTP was operated with the WTS sludge release. It was concluded that the sludge release in the sewage collection network is a viable alternative to disposal of the decanter's waste of WTP Actiflo®, not precluding the treatment of sewage in WWTP Verde and the use of sewage sludge in agriculture. However, can be necessary increase the UASB's sludge extraction frequency, from 16 hours of continuous duration of WTP sludge release in the sewage collection network.